2020
DOI: 10.3389/fneur.2020.00820
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption in Critical Illness

Abstract: Circadian rhythms play a vital role in metabolic, hormonal, and immunologic function and are often disrupted in patients in the ICU. Circadian rhythms modulate the molecular machinery that responds to injury and illness which can impact recovery. Potential factors contributing to the alteration in circadian rhythmicity in intensive care unit (ICU) patients include abnormal lighting, noise, altered feeding schedules, extensive patient care interactions and medications. These alterations in circadian rhythms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 63 publications
0
25
0
1
Order By: Relevance
“…Nowadays, the majority of scientists support the multi-oscillatory concept of regulation of the circulatory system of mammals with a central oscillator in the suprachiasmatic nucleuses of hypothalamus (CNS) -«the master clock» and the main humoral modulator -pineal gland, which performs its chronobiotic function by melatonin which is a "sleep hormone" [6,7,[16][17][18][19][20][21][22]. The physiological significance of melatonin is manifested in the synchronization of different biological processes according to day-and night-time illumination as well as during season changes.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Nowadays, the majority of scientists support the multi-oscillatory concept of regulation of the circulatory system of mammals with a central oscillator in the suprachiasmatic nucleuses of hypothalamus (CNS) -«the master clock» and the main humoral modulator -pineal gland, which performs its chronobiotic function by melatonin which is a "sleep hormone" [6,7,[16][17][18][19][20][21][22]. The physiological significance of melatonin is manifested in the synchronization of different biological processes according to day-and night-time illumination as well as during season changes.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Also, we now know that disease condition can alter baseline characteristics. Studies in critical care patients whose circadian rhythms are effectively abolished ( 99 ) have shown that the circadian PK/PD behavior of pharmaceuticals tends to diminish ( 100 ).…”
Section: The Circadian Basis Of Chronopharmacologymentioning
confidence: 99%
“…G A Richards, 1 MB BCh, PhD, FCP (SA), FRCP, MASSAf; OrcID 0000-0002-8893-3934; A Bentley, 2 MB BCh, PhD; OrcID 0000-0001-6533-5213; P D Gopalan, 3 MB ChB, PhD, FCA (SA), Crit Care (SA); OrcID 0000-0002-3816-1171; L Brannigan, 4 MB BCh, DA (SA), FCA (SA), Cert Crit Care (SA); OrcID 0000-0002-6215-254; F Paruk, 5 MB BCh, PhD, FCOG (SA), Cert Crit Care (SA); OrcID 0000-0002-6259-0106 are controlled by the SCN by influencing the timing of feeding and activity as well as regulating the rhythmic release of hormones. [18] Ideally, both the central and peripheral clocks should be aligned and environmental factors should synchronise these internal clocks with the external environment. These clocks may be disconnected in some circumstances such as with sepsis [17] and with changes in the external environment, such as flight over time zones or the disruptive ICU environment, which can temporarily desynchronise internal clocks from the external environment.…”
Section: Melatonin Sleep and The Icumentioning
confidence: 99%
“…There are also tissue specific peripheral clocks in all cells including immune cells such as macrophages, which are controlled by the SCN by influencing the timing of feeding and activity as well as regulating the rhythmic release of hormones. [18] …”
Section: Melatonin Sleep and The Icumentioning
confidence: 99%
See 1 more Smart Citation